Cellulosic Textile Pretreatment Application with Alkali Active Catalase from Serratia marcescens - C., Govindaraj; R., Ugamoorthi; S., Ramarethinam (International Journal of Scientific Research in Biological Sciences, 2020)
Preliminary treatment is a process for the extract of natural and added adulteration present in textile fibres to enhance the absorbency. Cotton pretreatment formula includes the Sodium hydroxide, and Hydrogen peroxide to eliminate the non-cellulosic polluting influences and characteristic shading matter. Hydrogen peroxide was profoundly utilized as a fading operator in the pretreatment of cellulosic and protein filaments. The lingering peroxide must be eliminated before the texture was exposed to coloring since it may meddle with the coloring cycle. Hence, compound peroxide executioners were utilized to get the texture before coloring eliminate the leftover peroxide. As another contagious catalase was utilized for killing the leftover peroxide, which acts just at acidic pH. This current investigation uncovers the utilization of catalase by Serratia marcescens, which has action on both acidic and antacid pH. The higher movement of catalase was screened by utilizing various mediums. Reactor preliminaries were performed to discover the specific boundaries for the creation of high catalase movement with low pigmentation and for medium advancement. Compound steadiness was concentrated by utilizing diverse pH and temperatures to plan the material application measure by utilizing catalase as a neutralizer to decrease steps and spare vitality.